The Study of Nonlinear Optical Properties of Curcumin Dye Using Z-Scan Method - MUKHTAR, MAS IEZATY; ADNAN, NURUL NADIA; KRISHNAN, GANESAN (Enhanced Knowledge in Sciences and Technology, 2024)
Curcumin, a prominent component in Curcuma longa’s rhizome, manifests as a vibrant orange-yellow crystalline compound. This research uses the Z-scan technique to characterise the nonlinear refractive (NLR) and nonlinear absorption (NLA) of Curcumin dye solutions. Employing open and closed aperture in Z-scan measurements, we investigate the relationship between laser diode input fluences (150 mW) at five different dye concentrations (0.1 mM, 0.2 mM, 0.3 mM, 0.4 mM, and 0.5 mM). The results show that nonlinear refractive (NLR) and nonlinear absorption (NLA) were observed starting at 0.1 mM and going up to 0.5 mM. The result indicates the emergence of NLR and NLA properties from 0.01 mm, with a reduction in NLR value observed as concentrations increased. This underscores Curcumin dye’s potential as an optical limiter in photonics applications.